Hubungan Kemudahan Transaksi Pembayaran dan Promo Gratis Ongkos Kirim dengan Perilaku Impulsive Buying - Nugroho, Christian Adven; Prijowuntato, Sebastianus Widanarto (Jurnal Pendidikan Ekonomi dan Akuntansi, 2025)
This study aims to determine the relationship between the ease of payment tran-sactions and free shipping promos with the impulsive buying behaviour of Sanata Dharma University students. This research approach is quantitative. The research was conducted from February to April 2025. The study population was 9562 people. The research sample was 384 people. The research sampling technique employed was accidental sampling. The data collection method was a questionnaire. The research data analysis technique used the Kendall-Tau correlation. The results of this study indicate: 1) there is a relationship between the ease of payment transactions and impulsive buying behaviour in Sanata Dharma University students (correlation coefficient = 0.115; sig. (2-tailed) = .001). 2) there is a relationship between free shipping promos and impulsive buying behaviour in Sanata Dharma University students (correlation coefficient = 0.263; (2-tailed) = 0.000) 2) there is a relationship between free shipping promos and impulsive buying behaviour in Sanata Dharma University students (correlation coefficient = .263; sig.). (2-tailed) = .000)